23.1k views
2 votes
Solve the formula for the indicated variable-
S = L(1-r), for r

User AmeyaB
by
6.2k points

1 Answer

3 votes

Answer:

r=
-(S)/(L) +1

Explanation:

You would want to isolate the r by itself by doing all the opposite operations.

First, you can divide the L to get

1-r =
(S)/(L)

Next, move the 1 to the other side to get

-r=
(S)/(L) -1

Then, we would not want to keep the negative so, move it to the other side to get

r=
-(S)/(L) +1

(Note the 1 changed to a positive because we move the negative to the other side so, negative or negative 1 will be positive.

User Lang
by
5.9k points